Case Report of a Fatal Antifreeze Ingestion with a Record High Level and Impressive Renal Crystal Deposition - Heidi L. Erickson (Case Reports in Critical Care)
Ethylene glycol, methanol, and diethylene glycol are readily available in many household and commercially available products. While these alcohols are relatively nontoxic themselves, their acidic metabolites are toxic and can result in significant morbidity and mortality. Herein we report a lethal case of massive ethylene glycol ingestion in a suicide with a record high level (1254 mg/dL) and images of the histologic examination of the kidneys revealing impressive calcium oxalate crystal deposition. Autopsy findings also showed evidence of mild cerebral edema.